Women’s receptions of female characters on television, 2010- 2011 - Bahadır, Zehra. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2011., 2011)
This was an exploratory research study where qualitative data collection method was used. It aimed to explore how women who watch television at least two hours a day and lived in a metropolis received what was presented to them through television programs, and if they thought there was an influence of those receptions on their daily lives or not. Furthermore, it aimed to discover their opinions about this influence and what kinds of changes occurred in their lives. In the light of the criteria mentioned above, fifteen women with different demographic characteristics were interviewed in this study, and the data was evaluated within case and cross case analysis to find major and salient common themes. The findings first indicated that women regarded television as a relaxation tool that they spent their free time; that they watched in order to relax or follow certain programs. Secondly, it was found out that television was a socialization tool for women as they stated that they socialized through watching television and also they socialized with the people around by discussing the content of the programs. In terms of the reception of female characters on television, it was found that women built empathy and identification with their favorite characters while they did not like the characters they could not empathize with or the characters that lived just in an opposite way when compared to their own life styles. In addition, in terms of reception of the effect of character on personal life and character as a role model, all the participants remarked that they certainly believed that women on television had an effect on the lives of viewers; however, whereas twelve participants stated that the characters had a direct effect on their lives or they always did comparisons with the characters or took them as role models, three of them said that they could not say they took any character as a role model in their own personal lives. Lastly, about women representation on television, all of the participants stated that they thought women in general were represented both positively and negatively and these bothsided representations might affect women who watched these female characters. In conclusion, all these receptions could be regarded as informal learning as all the participants agreed that things on television certainly had an influence on the viewers to some extent. This influence could be seen in different areas leading to a change in the end.
Keywords: Television and women.; Television viewers.; Television criticism.